Seroprevalence of Hepatitis B Virus and Associated Factors among Pregnant Women Attending Antenatal Care Services at Public Health Facilities in Nekemte Town - Sinkinesh Eba; Gemechu Kejela; Afework Tamiru (Hindawi Limited, 2021)
Background. Viral hepatitis is an emerging global health problem. A pregnant mother infected with the hepatitis B virus has a high rate of vertical transmission, causing adverse fetal and neonatal outcomes. Understanding the magnitude of the problem and associated factors has paramount importance to avert such adverse fetal and neonatal outcomes. Therefore, the main aim of this study was to assess the seroprevalence of hepatitis B virus and associated factors among pregnant women attending antenatal care clinics at public health facilities in Nekemte town. Methods. An institutional-based cross-sectional study was conducted among 277 pregnant women attending antenatal care at public health facilities in Nekemte town from June 1 to July 30, 2020. All public health institutions in Nekemte town (two hospitals and one health center) were recruited, and study participants were selected by using a systematic sampling method. The data were collected using pretested and structured questionnaires using a face-to-face interview, and a blood sample was collected to test for hepatitis B surface antigen. Logistic regression analysis was employed to identify factors significantly associated with hepatitis B virus infection. Variables with a p value < 0.05 were considered statistically significant predictors of the outcome variable. Result. The overall seroprevalence of hepatitis B virus infection was 16 (5.8%) [95% CI: 3.2-8.7], which indicates intermediate endemicity. History of abortion (AOR =6.155; 95% CI: 1.780, 21.291), history of contact with hepatitis patient (AOR =7.178; 95% CI: 1.702, 30.279), and having multiple sexual partners (AOR =6.788; 95% CI: 1.701, 27.086) had a statistically significant association with hepatitis B surface antigen seropositivity. Conclusion. Hepatitis B virus seroprevalence among pregnant women in this study shows intermediate endemicity. Therefore, health professionals should provide health information on the risk of having multiple sexual partners, risk factors of unprotected contact with hepatitis patients, and abortion for pregnant women during their antenatal care visits.